Advanced Ureteroscopy A Practitioner's Guide to Treating Difficult Problems - Hubosky, Scott G.; Grasso III, Michael; Traxer, Olivier; Bagley, Demetrius H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book considers all aspects of ureteroscopy and the dominant role that it plays in the treatment of many urologic disorders. Most diseases of the ureter and renal collecting system must be considered for ureteroscopic diagnosis and/or treatment. This book explores advancements of instrumentation such as endoscopes, ancillary devices, endoscopic lithotripters, and ablative devices. It also illuminates the most current diagnostic and therapeutic techniques, including pre- and postoperative treatment, metabolic management, and the role of chemotherapy in the upper tract. Further, this book examines less common indications for ureteroscopy such as strictures, foreign bodies, and diagnostic dilemmas. Organized by situation or diagnosis, this book considers all treatment options and notes the role of ureteroscopy before exploring technical approaches, goals of treatment, detailed techniques, staged treatments, potential complications, and postoperative management. Advanced Ureteroscopy: A Practitioner's Guide to Treating Difficult Problems is the definitive source for the endoscopic approach to common and rare upper tract diseases, serving urologic endoscopists, practicing urologists, residents, and fellows.
Difficult Acess to the Ureter -- Imaging of the Upper Urinary Tract -- Ureteroscope Specifications: Flexible, Semirigid and Single-Use -- Robotic Platforms for Ureteroscopy -- Guidewires -- Ureteral Access Sheaths -- Stone Retrieval Devices -- Basic Techniques: Fundamental Maneuvering During Ureteroscopy -- Basic Techniques of Ureteroscopy: No-Touch Ureteroscopy -- Safety Considerations During Ureteroscopy -- Ureteral Stone Treatment -- Flexible Ureteroscopic Treatment of Renal Stones -- Post Ureteroscopic Evaluation: Short and Long Term -- Selection and Need for Metabolic Evaluation -- Diagnosis of Upper Tract Urothelial Carcinoma -- Enhanced Endoscopic Imaging Techniques for Upper Tract Urothelial Carcinoma -- Ureteroscopic Treatment of Upper Tract Urothelial Carcinoma -- Adjuvant Treatment for Upper Tract Urothelial Carcinoma: Topical and Systemic -- Ureteroscopic Management of Upper Urinary Tract Obstruction -- Ureteroscopic Treatment of Chronic Unilateral Hematuria -- Antegrade Ureteroscopy -- Complications of Ureteroscopy.
Keywords: Urology; Urology; Ureteroscopy -- methods; Ureteral Diseases -- diagnosis; Ureteral Diseases -- surgery